2014
DOI: 10.1055/s-0034-1370633
|View full text |Cite
|
Sign up to set email alerts
|

Third Ventricular Glioblastoma Multiforme: Case Report and Literature Review

Abstract: BackgroundGBM is an intra-axial mass, localized to the frontotemporal region that accounts for 50 to 60% of astrocytomas and 12 to 15% of intracranial tumors. It is found most commonly as a primary tumor, with secondary tumor characteristics as result of transformation from low-grade glioma. 1-8 Intraventricular tumors represent only 10% of central nervous system neoplasms. Of those, the reported malignancy rate is 13% of all cases. Lee and Manzano enumerated the most frequently found ventricular system tumors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The peculiar distribution following only the ependymal lining instead of white matter tracts is anecdotic, but it may support the hypothesis that the glioblastomas’ cell of origin (COO) is a neural precursor cell located in the subventricular zone (SVZ) along the lateral ventricular walls. Lee and Manzano stated that possible alternative origins of intraventricular glioblastomas could be the septum pellucidum or the fornix, both components of the limbic system [ 2 ]: the involvement of these structures could explain the growing number of amnesic episodes in the clinical history of our case, neurological finding which is, in fact, characteristic of other intraventricular glioblastoma cases reported in literature [ 3 ]. However, the most common symptoms associated with intraventricular glioblastomas appear to be related to obstructive hydrocephalus, which surely could be a cause or a concurrent cause to both the initial symptoms of our case.…”
mentioning
confidence: 81%
“…The peculiar distribution following only the ependymal lining instead of white matter tracts is anecdotic, but it may support the hypothesis that the glioblastomas’ cell of origin (COO) is a neural precursor cell located in the subventricular zone (SVZ) along the lateral ventricular walls. Lee and Manzano stated that possible alternative origins of intraventricular glioblastomas could be the septum pellucidum or the fornix, both components of the limbic system [ 2 ]: the involvement of these structures could explain the growing number of amnesic episodes in the clinical history of our case, neurological finding which is, in fact, characteristic of other intraventricular glioblastoma cases reported in literature [ 3 ]. However, the most common symptoms associated with intraventricular glioblastomas appear to be related to obstructive hydrocephalus, which surely could be a cause or a concurrent cause to both the initial symptoms of our case.…”
mentioning
confidence: 81%
“…29,30,39,46,47 Glioblastoma multiforme (GBM) is the most common and most aggressive of malignant primary CNS tumors 37 and has been the center of attention for multiple HIFU trials. In an article published in 2006, Ram et al 69 reported on 3 patients with GBM who underwent MRgHIFU thermal ablation.…”
Section: Tumor Thermocoagulationmentioning
confidence: 99%